2017
DOI: 10.1007/s11548-017-1637-y
|View full text |Cite
|
Sign up to set email alerts
|

3D Boolean operations in virtual surgical planning

Abstract: The proposed method of Boolean operations, BORES, is efficient and appropriate for virtual surgical planning. Moreover, it is simple and easy to implement. In future work, we will extend the proposed method to handle non-colliding components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Only a few authors have reported on comparable digital matching approaches to evaluate bone grafting procedures [37][38][39]. Surface matching and Boolean subtraction, as performed in this study, are known to be a reliable technique of high precision in craniofacial surgical planning [18,40]. Hence, future clinical studies could profit from this technique as it could provide additional information and more accurate data.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Only a few authors have reported on comparable digital matching approaches to evaluate bone grafting procedures [37][38][39]. Surface matching and Boolean subtraction, as performed in this study, are known to be a reliable technique of high precision in craniofacial surgical planning [18,40]. Hence, future clinical studies could profit from this technique as it could provide additional information and more accurate data.…”
Section: Discussionmentioning
confidence: 97%
“…Cone beam computed tomography (CBCT) has become routine in digital radiographic diagnostics and is recommended as routine prior to treatment involving dental implants and bone augmentation procedures [16]. In a staged approach, CBCT scans are used prior to bone augmentation to evaluate the anatomy of the defect, including the adjacent anatomical structures and after healing of the site, in order to plan for the ideal implant position [17,18]. Hence, CBCT scans routinely taken during treatment provide an option to evaluate the amount of bone that has been augmented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes 3D surgical simulations and designs of cutting guides and plates pre-formed to the desired postoperative position. Occlusal splints may be virtually constructed through a simple Boolean operation (Charton et al, 2017), whereby the incisal and cuspal regions of the upper and lower dentition are removed from a virtual blank splint.…”
Section: D-vsp Protocol For Orthognathic Surgerymentioning
confidence: 99%